Trends of volatile chlorinated hydrocarbons and trihalomethanes in Antarctica - INSOGNA, SUSANNA; MARCONI, ELISABETTA; BACALONI, Alessandro; S. Frison (International Journal of Environmental Analytical Chemistry, 2014)
In order to understand behaviour and environmental fate of manmade chemicals in remote and cold areas, during the XXVII Italian Expedition carried out in Antarctica throughout the austral summer 2011/2012, superficial snow and lake water were sampled along the Ross Sea's South coast and their content of some low-molecular weight volatile halogenated hydrocarbons was evaluated. In consideration of their important role in stratospheric ozone chemistry, some volatile chlorinated hydrocarbons (VCHCs) and trihalomethanes (THMs) were investigated. The analyses were realised with a dedicated system composed by a purge-and-trap injector coupled to a gas chromatograph with a mass spectrometer (PTI-GC-MS) operating in SIM mode. The investigated VCHCs (chloroform; 1,1,1-trichloroethane; tetrachloromethane; trichloroethylene and tetrachloroethylene) were present in all analysed samples, and concentration levels ranged from units to hundreds of ng L−1 according to considered matrix. For the first time, THMs (bromoform; dibromochloromethane; bromodichloromethane), were measured in Antarctic lake waters and freshly deposited snow; their concentration levels ranged from units to tens of ng L−1. In order to assess eventual temporal variations, VCHC content in aqueous Antarctic matrices was compared with levels occurring in the past Italian Antarctic expeditions: for some banned substances, a decrease in concentration was observed, probably due to worldwide use restrictions. Finally, current Antarctic and Italian VCHC and THM levels in snow and lake water samples were compared and were found to be quite similar, differing at most by one order of magnitude, corroborating the hypothesis of an accumulation of halogenated compounds in Antarctic aqueous matrices.